Predicting Length of Stay and Readmissions After an Ankle Fracture Using a Risk Stratification Tool (STTGMA). Issue 11 (November 2020) - Simske, Natasha M.; Benedick, Alex; Kavanagh, Michael D.; Vallier, Heather A.
Abstract : Objectives: To determine the usefulness of a validated trauma triage score to stratify short-term outcomes including hospital length of stay (LOS), in-hospital complications, discharge location, and rate of readmission after an ankle fracture. Design: Retrospective cohort. Setting: Level 1 trauma center. Patients: Four hundred fifteen patients, age ≥55 with 431 ankle fractures. Intervention: Closed or open reduction. Main Outcome Measurements: Score for Trauma Triage in the Geriatric and Middle-Aged (STTGMA). Results: Of the 415 patients, 38% were male, 72% were white, and the mean age was 66 years. The mean LOS was 4.4 days, and this increased from 2.6 days in the minimal-risk group to 11.8 days in the high-risk group ( P < 0.001). Similarly, 74% of minimal-risk patients were discharged home versus 13% of high-risk patients ( P < 0.001). There were 19 readmissions (4.6%) within 30 days, ranging from 1.5% to 10% depending on the risk cohort ( P = 0.006). Seventy-three patients (18%) experienced an in-hospital complication. On multiple linear regression, moderate- and high-risk STTGMA stratification was predictive of a longer hospital LOS, and moderate-risk STTGMA stratification was predictive of subsequent readmission after injury. Conclusions: Calculation of the STTGMA score is helpful for stratifying patients according to hospital LOS and readmission rates, which have substantial bearing on resource utilization and cost of care. The STTGMA tool may allow for effective identification of patients to potentially ameliorate these common issues and to inform payers and policymakers regarding patients at risk for greater costs of care. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.